2008
DOI: 10.1007/s00535-008-2160-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical diagnosis of gastric cancer using near-infrared multichannel Raman spectroscopy with a 1064-nm excitation wavelength

Abstract: The present results indicate that near-infrared multichannel Raman spectroscopy with a 1064-nm excitation wavelength is useful for gastric cancer diagnosis. Establishment of a Raman diagnostic system for gastric cancer may improve the clinical diagnosis of gastric cancer and be beneficial for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…We have previously reported, using biopsy specimens, the usefulness of Raman spectroscopy (RAS) as a novel diagnostic modality for gastric cancer [8]. The concept of RAS was originally established by Raman, C. V., in 1928 [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported, using biopsy specimens, the usefulness of Raman spectroscopy (RAS) as a novel diagnostic modality for gastric cancer [8]. The concept of RAS was originally established by Raman, C. V., in 1928 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…RAS is especially suitable for in vivo measurements because the power of the excitation light does not affect the tissue and the penetration depth is relatively large [10]. In our previous study, we utilized near-infrared RAS that had an excitation wavelength of 1064 nm [8]. Although the 1064 nm near-infrared multichannel RAS system appeared to have the potential to be a realtime diagnostic tool for gastric cancer in our previous study using biopsy specimens, the study might not have reflected in vivo use of RAS due to a lack of tissue other than the mucosal layer in the biopsy specimens.…”
Section: Introductionmentioning
confidence: 99%
“…RS of tissue has been reported at wavelengths from the ultraviolet 17 to 1064 nm in the infrared. 18 Typically, sources in the near-infrared are preferred because tissue autofluorescence is reduced. However, Raman scattering intensity and detector responsivity also typically decrease with increasing wavelength.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have confirmed the accuracy of the diagnostic technique based on Raman spectroscopy in various biological tissues such as the cervical lesions [1,22], gastric tissues [15,30], colon [20], thyroid [18], larynx [34], skin [2,17], bladder [6,10], among others. In prostate tissues, several studies indicated the diagnostic capability of various optical techniques [5,7,9,33].…”
Section: Introductionmentioning
confidence: 90%
“…PCA has been employed for spectral classification in a variety of diseases such as atherosclerosis and neoplasias, among others [9,10,[13][14][15]17,20,26,27,34,35]. With PCA, one could separate the relevant spectral information which is dependent on the composition of the material analyzed, i.e., a few variables, from the random, uncorrelated variations.…”
Section: Introductionmentioning
confidence: 99%